HPV and Chlamydia trachomatis co‐detection in young asymptomatic women from high incidence area for cervical cancer. Issue 11 (18th August 2014) - Bellaminutti, Serena; Seraceni, Silva; De Seta, Francesco; Gheit, Tarik; Tommasino, Massimo; Comar, Manola
<x xml:space="preserve">Abstract</x> Chlamydia trachomatis causing chronic inflammatory diseases has investigated as possible human papillomavirus (HPV) cofactor in cervical cancer. The aim of this study is to evaluate the prevalence of Chlamydia trachomatis and HPV co‐infection in different cohorts of asymptomatic women from a Northern Italy area at high incidence for cervical cancer. Cervical samples from 441 females were collected from Cervical Cancer Screening Program, Sexually Transmitted Infectious and Assisted Reproductive Technology centres. HPV and Chlamydia trachomatis were detected simultaneously and genotyped using a highly sensitive bead based assay. The overall prevalence of Chlamydia trachomatis was estimated 9.7%, in contrast with the reported national data of 2.3%, and co‐infection with HPV was diagnosed in the 17% of the samples. In females ≤ 25 years of age, the infection reached a peak of 22% and co‐infection with HPV of 45.8% (P < 0.001). Of note, in young females diagnosed with low grade cervical lesions, no significant difference between Chlamydia trachomatis and HPV distribution was observed, while differently, HPV co‐infection was found significantly associated to the presence of intraepithelial lesions when compared to older females (20% vs. 1%; P < 0.001). In this study, the use of a high sensitive molecular technique exhibited higher analytical sensitivity than the referred assays for the diagnosis of Chlamydia trachomatis and HPV co‐infection in asymptomatic females, leading to reduction of the potential to identify incorrectly the infection status. An active screening for timely treatment of Chlamydia trachomatis infection is suggested in young females to evaluate a possible decrease in incidence of pre‐cancer intraepithelial lesions. J. Med. Virol. 86:1920–1925, 2014. © 2014 Wiley Periodicals, Inc.